Efeito do tempo e temperatura de envelhecimento na microestrutura do aço inoxidável super duplex UNS S32760-F55 - Artimonte, João Felipe (Universidade Federal de São Carlos, 2024)
Super Duplex Stainless Steels (SDSS) are widely employed in environments with aggressive conditions in oil and gas, petrochemical, paper and pulp, and other industries due to their high strength, toughness, and corrosion resistance properties. The development of duplex stainless steels (DSS) has resulted in complex steel compositions to achieve the requirements of microstructure and properties, because of it, undesirable intermetallic phases can precipitate due to the high amount of alloying elements in these steels when exposed to high temperatures during welding, forging, hot working, and aging. The aim of this study is to investigate the precipitation of intermetallic phases in the SDSS UNS S32760-F55. Samples were isothermally aged at different temperatures between 500 and 900ºC for 10-6000 minutes, followed by water quenching. The results showed that sigma and chi phases precipitation rate increases with the increase in temperature, so that these phases precipitate at shorter times as the temperature increases from 500 to 900ºC. Other phases, such as chromium nitrides, precipitate at lower temperatures. Chromium nitrides at ferrite/ferrite interfaces were observed at 500ºC after 30 minutes exposure, and no sigma phase was observed in the steel at the 500ºC aging.
Effect of aging time and temperature on the microstructure of super duplex stainless steel UNS S32760-F55.
Keywords: Aços Inoxidáveis Duplex; Microestrutura; Envelhecimento; Fases intermetálicas; Fase sigma; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA